Pengaruh Promosi Melalui Media Sosial dan Word of Mouth Terhadap Minat Kunjungan Ulang Pasien - Febiana, Ceria; Putri Wijayanti, Anita; Winarti, Wiwin; Hanafi, Mutiafani (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The purpose of this study was to determine the effect of promotions through social media and word of mouth on the intention to revisit PINDAD Hospital patients, with a patient population of PINDAD Hospital with a sample of 100 respondents taken by purposive sampling method. Data was collected by distributing questionnaires directly and also using the Google form. After the validity and reliability tests were carried out, the analysis was carried out with the classical assumption test, multiple linear regression analysis tests, the coefficient of determination, the f test and t test. The results showed that promotions with social media and word of mouth had a positive and significant effect on patient repeat visits, which means that if promotions with social media and word of mouth were increased, the patient's repeat visits would also increase significantly.